Degradation of metaldehyde in water by nanoparticle catalysts and powdered activated carbon - Li, Zhuojun; Kim, Jong Kyu; Chaudhari, Vrushali; Mayadevi, Suseeladevi; Campos, Luiza C. (Environmental Science and Pollution Research, 2017)
Metaldehyde, an organic pesticide widely used in the UK, has been detected in drinking water in the UK with a low concentration (< 1 mu g L-1) which is still above the European and UK standard requirements. This paper investigates the efficiency of four materials: powdered activated carbon (PAC) and carbon-doped titanium dioxide nanocatalyst with different concentrations of carbon (C-1.5, C-40, and C-80) for metaldehyde removal from aqueous solutions by adsorption and oxidation via photocatalysis. PAC was found to be the most effective material which showed almost over 90% removal. Adsorption data were well fitted to the Langmuir isotherm model, giving a q (m) (maximum/saturation adsorption capacity) value of 32.258 mg g(-1) and a K-L (Langmuir constant) value of 2.013 L mg(-1). In terms of kinetic study, adsorption of metaldehyde by PAC fitted well with a pseudo-second-order equation, giving the adsorption rate constant k(2) value of 0.023 g mg(-1) min(-1), implying rapid adsorption. The nanocatalysts were much less effective in oxidising metaldehyde than PAC with the same metaldehyde concentration and 0.2 g L-1 loading concentration of materials under UV light; the maximum removal achieved by carbon-doped titanium dioxide (C-1.5) nanocatalyst was around 15% for a 7.5 ppm metaldehyde solution.

Adsorption of heavy metal on active carbon derived from coconut leaves agro-waste - Jadhav, Abhijit; Mohanraj, Govindaraj; Mayadevi, Suseeladevi; Gokarn, Ashok (Chemistry & Chemical Technology, 2020)
In this paper activated carbon is prepared from coconut leaves by chemical activation during slow pyrolysis at 673 K in an inert atmosphere. Activated carbon is prepared in the stiochiometric ratio of 1:1 (CL1), 2:1 (CL2) and 3:1 (CL3). Optimized 3:1 ratio is preferable for further study. BET surface area of CL3 activated carbon was found 1060.57 m2/g. It is greater than those of CL1 and CL2. The batch sorption study experiments were conducted with respect to solute concentration of 2.5–122.8 mg/l and solution temperature of 313–343 K. The Langmuir, Freundlich and Temkin isotherm studies were conducted. The experimental data fitted very well for the pseudo-first order and pseudo-second-order. The results have established good potentiality for the CL3 activated carbon to be used as a sorbent for the removal of lead from wastewater.

Degradation of metaldehyde in aqueous solution by nano-sized photocatalysts and granular activated carbon - Kim, Jong Kyu; Jiang, Tingting; Li, Zhoujun; Mayadevi, Suseeladevi; Bharat, Kale; Joo, Jin Chul; Campos, Luiza Cintra (Journal of Nanoscience and Nanotechnology, 2020)
Metaldehyde has been detected in drinking water system in relatively high concentration exceeding European water quality standard. In order to address this problem, the aim of this project was to treat metaldehyde aqueous solution by advanced oxidation processes (AOPs) and granular activated carbon (GAC) column. Ten novel materials were tested for degradation rates of metaldehyde under ultraviolet light irradiation (UVC). For treatment of 1 mg/L metaldehyde solution by AOPs, the highest degradation rate is 16.59% under UVC light with the aid of nitrogen doped titanium dioxide coated graphene (NTiO2/Gr). Furthermore, 0.5 mg/L is the optimal concentration for degradation of metaldehyde with N-TiO2/Gr under UVC light. Apart from that, the lifetime of GAC column could be elongated on condition that metaldehyde has been treated by AOPs previously. Hence, combination of AOPs and GAC column is promising in treating water containing metaldehyde.